Telerehabilitation for Chronic Low Back Pain: A Review of Current Evidence and Clinical Perspectives - Szeliga, Katarzyna; Sawin, Magda; Lorek, Julia; Waszkiewicz, Patrycja; Brzozowska, Wiktoria; Grobecki, Daniel; Jabłoński, Franciszek; Jabłońska, Hanna; Korybski, Jakub; Jarczak, Adam (Quality in Sport, 2026)
Background. Chronic low back pain (CLBP) is a widely prevalent and multifactorial condition defined as pain lasting more than 12 weeks, associated with functional limitations and increased healthcare burden. Despite recommended treatments, barriers such as limited access to care and time constraints may reduce adherence. Telerehabilitation has emerged as a promising approach enabling remote delivery of rehabilitation. Aim. The aim of this review was to evaluate current evidence and clinical perspectives on telerehabilitation in the management of chronic low back pain. Materials and Methods. A literature review was conducted using PubMed, Google Scholar and SpringerLink databases, including studies published between 2016 and 2026. Articles were selected based on predefined inclusion and exclusion criteria and analyzed qualitatively. Results. Available evidence indicates that telerehabilitation may reduce pain intensity and improve functional outcomes in individuals with chronic low back pain, with effects generally comparable to conventional physiotherapy. High adherence, completion rates and patient satisfaction support its feasibility. Telerehabilitation may also improve access to care and reduce time and healthcare costs. However, results remain heterogeneous and depend on intervention type and delivery mode. Conclusions. Telerehabilitation appears to be a practical alternative or adjunct to face-to-face rehabilitation. Nevertheless, further high-quality studies are required to standardize interventions and confirm long-term effectiveness.